(3CNWGQ GdEOGQI (B/s - (3GjHdQ, eGQcs; (3GdYGeQj, NGdO s ((3GdbGgQI(B: s (3OGQ GdaGQhb ddfTQ hGdJhRjY(B, s, 2006)
(3jVe GdbjGOI, GdJhGUd, hLhO GdMGaR, EOGQI GdJZjjQ, JWhjQ TNUjI GdeOjQ, GdbOQI Ydi Md GdeTcdGJ, NOeI GdYedGA, JMbjb fJGFL eKeQI aj GdYed, GdEOGQI GdYGeI, GdJNWjW, KbGaI GdTQcI, CSGSjGJ GdYed, CcHQ GdCNWGA hCgegGs
Keywords: (3GdEOGQIs; (3GdEOGQI (B- (3GdCNWGAs; (3GdbjGOIs